2019
DOI: 10.1111/idj.12460
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription in emergency dental service in Zagreb, Croatia – a retrospective cohort study

Abstract: Objectives To analyse prescription of antibodies in emergency dental service according to antibiotic type, working diagnosis, patient visit time and patient demographic characteristics. Additionally, prescription practices among individual dentists were analysed. Methods The data in this retrospective cohort study were collected from electronic medical records and analyzed using descriptive statistics. Statistical analyses were conducted using the chi‐square test and the Z‐test with post‐hoc Bonferroni adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
(70 reference statements)
4
19
0
Order By: Relevance
“…20 In contrast, no gender differences in prescribing dental antibiotics were found among Croatian and British Columbian patients. 8,21 Indeed, it might be a challenge to explain why gender differences in both dentists and patients influence antibiotic prescriptions in the present study. The data obtained in this study might not be sufficient to describe this difference.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…20 In contrast, no gender differences in prescribing dental antibiotics were found among Croatian and British Columbian patients. 8,21 Indeed, it might be a challenge to explain why gender differences in both dentists and patients influence antibiotic prescriptions in the present study. The data obtained in this study might not be sufficient to describe this difference.…”
Section: Discussionmentioning
confidence: 84%
“…Female dentists prescribed significantly more antibiotics than male dentists (30% and 28%, P = <0.0001, respectively). Likewise, Croatian female dentists prescribed significantly more antibiotics than male dentists (50.8% and 46.8%, P = <0.001, respectively), 8 while dentists' gender did not influence the prescription of antibiotics in the United States. 16 Moreover, our study concluded that male patients received significantly more antibiotics than female patients (36% and 25%, P = <0.0001, respectively).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations